INTEGRASI INTERACTIVE READ ALOUD BERBANTUAN LITERACY CLOUD DALAM PEMBELAJARAN MENYIMAK TEKS NARASI DI SEKOLAH DASAR - Ratri Eka Ningtyas; Mega Diana, Siska; Profithasari, Nindy; Destini, Frida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research problem in this study was that students’ listening skills in Indonesian language learning were not yet optimal. This study aimed to determine the effect of integrating Interactive Read Aloud assisted by Literacy Cloud on students’ listening skills in narrative text learning. A quasi-experimental method with a non-equivalent control group design was employed in this study. The research was conducted at SD Negeri 6 Metro Timur in the 2025/2026 academic year. The research sample consisted of the entire population, comprising 32 third-grade students, selected using a saturated sampling technique. Data were collected through two techniques: a test in the form of essay questions consisting of fifteen items and a non-test technique in the form of observation sheets. The results showed that the integration of Interactive Read Aloud assisted by Literacy Cloud had a significant effect on students’ listening skills in narrative texts.